2018
DOI: 10.3389/fphys.2018.00395
|View full text |Cite
|
Sign up to set email alerts
|

Longer Work/Rest Intervals During High-Intensity Interval Training (HIIT) Lead to Elevated Levels of miR-222 and miR-29c

Abstract: Aim: MicroRNA-222 (miR-222) and miR-29c have been identified as important modulators of cardiac growth and may protect against pathological cardiac remodeling. miR-222 and -29c may thus serve as functional biomarkers for exercise-induced cardiac adaptations. This investigation compared the effect of two workload-matched high-intensity interval training (HIIT) protocols with different recovery periods on miR-222 and -29c levels.Methods: Sixty-three moderately trained females and males (22.0 ± 1.7 years) fulfill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 76 publications
(125 reference statements)
4
25
0
Order By: Relevance
“…Although we did not observe a statistically significant difference in our study, miR-222 presented increased levels of expression in animals submitted to cerebral ischemia associated with physical exercise. Therefore, our results corroborated both with Schmitz et al (2018) and with Liu et al (2015). Both studies demonstrated the protective role of physical exercise with increased expression of miR-222 in the cardiovascular system that leads us to suggest a possible systemic vascular action of this miRNA also targeting cerebrovascular regeneration.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although we did not observe a statistically significant difference in our study, miR-222 presented increased levels of expression in animals submitted to cerebral ischemia associated with physical exercise. Therefore, our results corroborated both with Schmitz et al (2018) and with Liu et al (2015). Both studies demonstrated the protective role of physical exercise with increased expression of miR-222 in the cardiovascular system that leads us to suggest a possible systemic vascular action of this miRNA also targeting cerebrovascular regeneration.…”
Section: Discussionsupporting
confidence: 88%
“…Researchers point out the miRNAs as potential biomarkers for the different intensities of physical exercise training directly involved in various physiological processes and with different response depending on the intensity applied during the training (Schmitz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In time, as research in this field progresses, it may be possible to match specific miRNAs to a specific molecular process; here, coaches will be able to understand whether the desired training effects-such as an increase in mitochondrial biogenesis-are actually occurring. We are close to the starting line here; the identification of miR-222 and -29c as drivers of cardiac adaptations following exercise illuminates the potential utility of monitoring the concentrations of these miRNAs-should an individual not see an elevation in these miRNAs, then training intensity/duration may have to be modified to elicit such a change [96]. Additionally, lower concentrations of miR-33 are associated with greater activation of AMPK following aerobic training [102], and miR-29b alters PGC-1α production [103]-both molecular signals for mitochondrial biogenesis-again demonstrating how real-time monitoring of miRNA concentrations could allow coaches to understand the specific adaptations an exercise is stimulating.…”
Section: Mirnasupporting
confidence: 55%
“…Taken together, it seems likely that miRNA-222 may indeed have cardioprotective effects in adult animals (and potentially humans) and in certain disease conditions such as heart failure rather than being detrimental. Several studies have shown that miRNA-222 may be specifically induced by physical exercise not only in athletes ( 10 12 ) but also in moderately trained healthy individuals ( 13 ) as well as patients with heart failure ( 8 ). It may therefore be of interest to initiate further studies to investigate to what extend miRNA-222 might be a useful marker to monitor cardioprotective exercise in primary and secondary prevention and rehabilitation of heart failure patients.…”
mentioning
confidence: 99%